2008
DOI: 10.1111/j.1467-7652.2008.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield assessment of integument‐led seed growth following targeted repair of auxin response factor 2

Abstract: Summary It is becoming increasingly vital to improve the yield of seed crops to feed an expanding population and, more recently, for biofuel production. One strategy to increase the yield is to increase the seed size, provided that there is not a concomitant decrease in seed number. In a previous study, we described a mutant in the AUXIN RESPONSE FACTOR 2 (ARF2) gene which produced extra cells in the seed coat and, subsequently, enlarged seeds. However, arf2 mutant plants also show severely reduced self‐fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…AUR62034763 is associated with flower morphogenesis and development and is a homolog of the Arabidopsis TF AUXIN RESPONSE FACTOR 2 ( ARF2 ). ARF2 is a pleiotropic developmental regulator (Okushima et al , ) associated with flower opening, fertility and seed yield in Arabidopsis (Hughes et al , ). The Arabidopsis arf2 mutant makes sepals grow longer, preventing petals from separating, so the flowers do not open, which then lowers seed set and yield (Hughes et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AUR62034763 is associated with flower morphogenesis and development and is a homolog of the Arabidopsis TF AUXIN RESPONSE FACTOR 2 ( ARF2 ). ARF2 is a pleiotropic developmental regulator (Okushima et al , ) associated with flower opening, fertility and seed yield in Arabidopsis (Hughes et al , ). The Arabidopsis arf2 mutant makes sepals grow longer, preventing petals from separating, so the flowers do not open, which then lowers seed set and yield (Hughes et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…ARF2 is a pleiotropic developmental regulator (Okushima et al , ) associated with flower opening, fertility and seed yield in Arabidopsis (Hughes et al , ). The Arabidopsis arf2 mutant makes sepals grow longer, preventing petals from separating, so the flowers do not open, which then lowers seed set and yield (Hughes et al , ). As flower development was delayed in quinoa treatments with yield losses (HS and HRS; Figure c) and transcription factors differentially expressed in these treatments are associated with flower development, it is possible that flower development may have a significant role in yield losses with shoot heat treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The ARF gene family has been repeatedly associated with flower and fruit maturation and development [61-63]. For instance, the arf2 mutants presented enlarged rosette leaves, thickened inflorescence stems, delayed flowering and senescence, reduced fertility and increased seed size [64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…High temperature causes infertility in Arabidopsis (Bac-Molenaar et al, 2015), and we found that 30°C is approaching the higher temperature threshold for Col-0. This may explain the reduction in seed set, which also is known to lead to an increase in seed size (Hughes et al, 2008).…”
Section: Temperature Influences the Oil Content Of Arabidopsis Seedsmentioning
confidence: 99%